TEACHERS’ VOICE IN ‘ASESMEN KOMPETENSI MINUMUM’: NAVIGATING THE CHALLENGES IN PRIMARY EDUCATION - Raynesa Noor Emiliasari; Yanty Wirza (Universitas Majalengka, 2024)
This study investigates the challenges encountered by public and private elementary school teachers in urban and rural areas when applying the Asesmen Kompetensi Minumum (AKM). This study employed a qualitative phenomenological method, interviewing four teachers from various circumstances. The findings reveal a number of challenges, including an increased workload, pressure to achieve high AKM scores, limited access to professional development, contradicting holistic education values, feelings of isolation, and policy ambiguity. These variables have a direct effect on teacher emotional well-being, motivation, and instructional efficacy. Teachers are expected to overcome these obstacles with more support from schools and the government, such as continuous training, collaboration rooms, and emotional support.